Game-based learning in medical education - Xu, Maosen; Luo, Yong; Zhang, Yu; Xia, Ruolan; Qian, Hong; Zou, Xiuhe (Frontiers in Public Health, 2023)
At present, medical education is rapidly evolving. Game-based learning (GBL) has been gradually used for education and several innovations have emerged. The emergence of serious game and gamification provides alternative approaches for educators to improve medical teaching process. Both serious game and gamification exert their education promoting function by providing the possibility of combining learning activity such as feedback, testing and spaced repetition with active participation and autonomy as well as positive experiences to students. Developing effective GBL modalities has the potential to bring immersive experience for medical students and improve their study outcomes. Herein, reviewed recent studies employing GBL in medical education, including serious games and gamification teaching. Furthermore, we also discuss the effectiveness and limitations of GBL, with the aim to suggest future directions for the development and application of GBL in medical education.